Combined convection heat transfer in a porous lid-driven enclosure due to heater with finite length - Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2006)
A numerical work is performed to analyze combined convection heat transfer and fluid flow in a partially heated porous lid-driven enclosure. The top wall of enclosure moves from left to right with constant velocity and temperature. Heater with finite length is located on the fixed wall where its center of location changes along the walls. The finite volume-based finite-difference method is applied for numerical experiments. Parameters effective on flow and thermal fields are Richardson number, Darcy number, center of heater and heater length. The results are shown that the best heat transfer is formed when the heater is located on the left vertical wall. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: combined convection; lid-driven cavity; porous medium